Prevalence of Cryptosporidium Carriage and Disease in Children With Primary Immune Deficiencies Undergoing Hematopoietic Stem Cell Transplant in Northern Europe. Issue 5 (May 2017) - Davies, Angharad P.; Slatter, Mary; Gennery, Andrew R.; Robinson, Guy; Crouch, Nigel; Elwin, Kristin; Hadfield, Stephen J.; Cant, Andrew J.; Davies, E. Graham; Chalmers, Rachel M.
Abstract : A prospective cohort study of children with primary immunodeficiencies undergoing hematopoietic stem cell transplant in the United Kingdom investigated the extent and significance of Cryptosporidium carriage in this high risk group. Three of 42 children recruited were infected with Cryptosporidium, a lower proportion than previously described. One had serious disease. The underlying immunodeficiency likely had a bearing on the clinical presentation and possible outcome of infection.